Agroecologia per nuovi paradigmi distrettuali integrati - Bocchi, Stefano (Scienze del Territorio, 2018)
Agroecology is a new sphere of thought and action embracing multiple dimensions: some scholars present it as a new science, others as crucible of experiences in motion, others as an integrated whole of knowledge and practices based on a new approach, required for transforming agro-food systems in the direction of sustainability and equity. Agroecology is all that and, for this reason, it can assume the structure and function of a new paradigm, rooted in systemic sciences and deploying them departing from production and consumption models. As such, agroecology lays the theoretical and practical foundation for entirely subverting the reductionist approach that produced the so called green revolution, started in North America in the middle of last century and still present in many spheres of our everyday acting and thinking. The characteristics of agroecology can sustain the desirable evolution of new concepts and the future developments of districts, which could shift from sector to multi-sector, taking on the role of drivers for the cultural, landscape and socioeconomic development of territories. In this framework, it is worth recalling some information related to: 1) features, processes, effects of the green revolution in Italy; 2) the new paradigm of agroecology; 3) guidelines for the development of the forthcoming multi-sector and integrated territorial districts.